Left ventricular function measurements in a mouse myocardial infarction model - Hendrikx, Geert; Bauwens, Matthias; Wierts, Roel; Mottaghy, Felix M.; Post, Mark J. (Nuklearmedizin - NuclearMedicine, 2016)
Aim: To assess the accuracy of ECG-gated micro (µ)-SPECT in a mouse myocardial infarction (MI) model in comparison to 3D-echocardiography. Animals, methods: In a mouse (Swiss mice) MI model we compared the accuracy of technetium-99m sestamibi (99mTc-sestamibi) myocardial perfusion, electrocardiogram (ECG) gated µSPECT to 3D-echocardiography in determining left ventricular function. 3D-echocardiography and myocardial perfusion ECG-gated µSPECT data were acquired in the same animal at baseline (n = 11) and 7 (n = 8) and 35 (n = 9) days post ligation of the left anterior descending coronary artery (LAD). Sham operated mice were used as a control (8, 6 and 7 mice respectively). Additionally, after day 35 µSPECT scans, hearts were harvested and 2,3,5-triphenyl-2H-tetrazolium chloride (TTC) staining and autoradiography was performed to determine infarct size. Results: In both infarcted and sham-operated mice we consistently found comparable values for the end-diastolic volume (EDV), end-systolic volume (ESV) and ejection fraction (EF) obtained by 3D-echocardiography and ECG-gated µSPECT. Excellent correlations between measurements from 3D-echocardiography and ECG-gated µSPECT were found for EDV, ESV and EF (r = 0.9532, r = 0.9693 respectively and r = 0.9581) in infarcted mice. Furthermore, comparable infarct size values were found at day 35 post MI by TTC staining and autoradiography (27.71 ± 1.80% and 29.20 ± 1.18% with p = 0.43). Conclusion: We have demonstrated that ECG-gated µSPECT imaging provides reliable left ventricular function measurements in a mouse MI model. Obtained results were comparable to the highly accurate 3D-echocardiography. This, in addition to the opportunity to simultaneously image multiple biological processes during a single acquisition makes µSPECT imaging a serious option for studying cardiovascular disease in small animals.
Keywords: ECG-gated SPECT; 3D-echocardiography; left ventricular function; myocardial infarction